2015
DOI: 10.1016/j.neuron.2015.10.030
|View full text |Cite
|
Sign up to set email alerts
|

ALS/FTD Mutation-Induced Phase Transition of FUS Liquid Droplets and Reversible Hydrogels into Irreversible Hydrogels Impairs RNP Granule Function

Abstract: SummaryThe mechanisms by which mutations in FUS and other RNA binding proteins cause ALS and FTD remain controversial. We propose a model in which low-complexity (LC) domains of FUS drive its physiologically reversible assembly into membrane-free, liquid droplet and hydrogel-like structures. ALS/FTD mutations in LC or non-LC domains induce further phase transition into poorly soluble fibrillar hydrogels distinct from conventional amyloids. These assemblies are necessary and sufficient for neurotoxicity in a C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
903
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 778 publications
(932 citation statements)
references
References 48 publications
26
903
3
Order By: Relevance
“…By analogy to hnRNPA1 (Molliex et al , 2015)‐, TDP‐43 (Conicella et al , 2016)‐, FUS (Murakami et al , 2015)‐, and C9orf72‐derived dipeptide repeats (Lee et al , 2016), tau LLPS could act to initiate tau aggregation in AD and FTD. We suggest that protein LLPS may be a biophysical mechanism underlying multiple protein aggregation and neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…By analogy to hnRNPA1 (Molliex et al , 2015)‐, TDP‐43 (Conicella et al , 2016)‐, FUS (Murakami et al , 2015)‐, and C9orf72‐derived dipeptide repeats (Lee et al , 2016), tau LLPS could act to initiate tau aggregation in AD and FTD. We suggest that protein LLPS may be a biophysical mechanism underlying multiple protein aggregation and neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…We recently showed that FUS LC maintains its primarily disordered structure within in vitro models of RNP granules (Burke et al , 2015). However, the high local concentration of proteins in RNP granules formed by LLPS may potentiate the conversion of liquid compartments into solid cytoplasmic aggregates and inclusions observed in disease (Murakami et al , 2015; Patel et al , 2015). This phenomenon may be enhanced by mutations in disease‐associated ribonuclear proteins that increase their cytoplasmic concentration (Vance et al , 2013) or aggregation propensity (Kim et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In the pathological process, the LC domains of the N terminus of TLS drives its phase transitions, reversibly shifting between dispersed, liquid droplet, and hydrogel-like phases [31,38,53]. The mutation of TLS severely limits this ability to repeatedly shift between these phases.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the mutated TLSs induce the propensity of TLS to condense into poorly soluble, stable, fibrillary hydrogel-like assemblies. These stably irreversible TLS aggregates, which selectively capture other RNA-binding proteins, impair local RNA-binding protein granule functions, and attenuate novel protein syntheses in the axon terminals of cultured neurons [31]. Modulation of these protein phase transitions might be a possible therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation